2010
DOI: 10.1111/j.1365-2095.2010.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold-pressed rapeseed cake as a component of the diet of common carp (Cyprinus carpio L.): effects on growth, nutrient utilization, body composition and meat quality

Abstract: The aim of the study was to determine the possibility of inclusion of cold‐pressed rapeseed cake (CPRC) in diets for common carp, Cyprinus carpio L. Four isonitrogenous (322 g kg−1 crude protein) and isoenergetic diets (17.5 MJ kg−1) with four levels of CPRC incorporation 0, 110, 220 and 330 g kg−1 (treatments RC0, RC11, RC22 and RC33, respectively) were evaluated in a 50‐day growth test with common carp of 500 g initial weight. Statistically significant higher final weights (1215–1243 g) were obtained in fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The quality assessment carried out showed significant differences in color brightness (L*, WI) and color redness (a*). In contrast, Mazurkiewicz et al (2011) did not report differences in the color components of fillets from carp fed varying levels of rapeseed oil and meals. In our study, the brightest color was observed in fillets from the control and CB2-fed groups, in which the largest muscle fibers and lowest muscle fat contents were also noted.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The quality assessment carried out showed significant differences in color brightness (L*, WI) and color redness (a*). In contrast, Mazurkiewicz et al (2011) did not report differences in the color components of fillets from carp fed varying levels of rapeseed oil and meals. In our study, the brightest color was observed in fillets from the control and CB2-fed groups, in which the largest muscle fibers and lowest muscle fat contents were also noted.…”
Section: Discussionmentioning
confidence: 68%
“…The highest protein content in the control fillets was probably due to the feed containing twice as much fishmeal as the fortified feeds (CB1-CB3). Mazurkiewicz et al (2011) did not show significant differences in the crude protein content of carp fed with different proportions of meal (fish, soybean, wheat) and rapeseed oil. Yet, together with an increase in meals and a decrease in rapeseed oil, these authors observed an increase in crude fat content.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…L * varied from 55.48 (ZA) to 66.24 (W‐M). Lightness of fish muscle depends mostly on fish species and is not influenced by environmental factors . Despite the lack of statistically significant differences, variations in lightness of carp meat were visible to consumers.…”
Section: Resultsmentioning
confidence: 95%
“…All fish were weighed at 10-day intervals according to Mazurkiewicz et al (2010) [54]. Prior to weighing, the fish were anesthetized by immersion in 130 mg/L tricaine methanesulfonate (MS–222, Sigma Aldrich) solution.…”
Section: Methodsmentioning
confidence: 99%